Formation of fine and encapsulated mefenamic acid form I particles for dissolution improvement via electrospray method - Zolkepali, Nurul Karimah; Abu Bakar, Noor Fitrah; Naim, M. Nazli; Anuar, Nornizar; Kamalul Aripin, Nurul Fadhilah; Abu Bakar, Mohd Rushdi; Lenggoro, I. Wuled; Kamiya, Hidehiro (Taylor & Francis, 2018)
The potential of using electrostatic atomizer or electrospray in producing fine and encapsulated particle of mefenamic acid (MA) form I with β-cyclodextrin (βCD) was demonstrated in this study. Encapsulated MA-βCD with a molar ratio of 1:2 was prepared in water-ethanol suspension, followed by the electrospray process to atomize the droplet into fine dried particles. The working distance (WD) between the electrospray needle tip and the substrate were varied from 15 to 25 cm. The sizes of encapsulated MA-βCD particles were found to decrease from 91 +- 26 to 42 +- 35 nm as the WD increased. The dissolution rate of encapsulated particles of MA-βCD was found to be higher compared to the particles of as-received MA and the unencapsulated MA. The presence of the encapsulated MA-βCD was proven by a thermal analysis with the disappearance of MA peak after the atomization process. The x-ray diffraction and FTIR analysis showed that the encapsulation occurred with the existence of new solid phase that was expected from interaction between MA and βCD and the appearance of C=C. Further analysis by transmission electron microscopy showed the size and morphology of MA-βCD particles when immersed in water and acetone. Encapsulated MA-βCD particles were solubilized in water but suspended as spherical shape in acetone.